New records of Scatopsidae (Diptera) from southeastern Mexico, and descriptions of new species of Swammerdamella Enderlein and Colobostema Enderlein - Huerta, Herón; Ibáñez-Bernal, Sergio (Zootaxa, 2008)
The following Scatopsidae species are recorded in Mexico by first time: Parascatopse flavida Cook, Thripomorpha chaboti Haenni and Rapp and Parascatopse sp., Colobostema hoffmannae sp. nov., Swammerdamella grogani sp. nov., and the female of Parascatopse flavida Cook are described.Keys words: Scatopsidae, Colobostema, Parascatopse, Swammerdamella, Thripomorpha, Mexico, distribution, new species